Randomized phase II placebo-controlled study to evaluate the efficacy of topical pure emu oil for joint pain related to adjuvant aromatase inhibitor use in postmenopausal women with early breast cancer: JUST (Joints Under Study) - Chan, Arlene; De Boer, R.; Gan, A.; Willsher, P.; Martin, R.; Zissiadis, Y.; Miller, K.; Bauwens, A.; Hastrich, D. (Springer, 2017)
© 2017, Springer-Verlag GmbH Germany. Purpose: Aromatase inhibitors are standard of care in women with hormone receptor-positive early breast cancer. Published evidence demonstrates that adverse effects may have an impact on drug compliance, with arthralgias being one of the most commonly reported adverse effects. Methods: Eligible patients were postmenopausal women who had experienced arthralgia following initiation of an aromatase inhibitor. Patients who experienced arthralgias following a minimum of a 3-month treatment on the aromatase inhibitor were randomized to emu oil or placebo oil. The primary endpoint was to assess for a reduction in pain as measured by a visual analogue score after 8 weeks of treatment. Results: Seventy-three patients comprised the intent-to-treat population, and there was no statistically significant benefit with use of EO. However, there was a statistically significant improvement in pain (visual analogue score was -1.28; p  <  0.001) and Brief Pain Inventory severity score -0.88 (p  <  0.001), as well as functional interference (Brief Pain Inventory interference -1.10 (p  <  0.001) for the entire population following an 8-week administration of EO or placebo oil. Conclusions: Arthralgias, as a result of aromatase inhibitor use, may be ameliorated by the use of topical oil massaged onto the joint. Further research into interventions for this common side effect is needed.